Le Bureau : Le nouveau mockumentaire d’entreprise francais(e) en question? - C(h)ris Reyns-Chikuma (TranscUlturAl, 2009)
In this essay, I show how Le Bureau (2006), a business fiction adapted from the British TV series The Office (2001-2003), maintained its originality by being in line with diverse traditions both French and trans-national. However, while addressing with a satirical tone some problems that are either global (like some issues related to the “new spirit of capitalism”) or typically French (such as the resistance to a concrete application of anti-discriminatory measures on the workplace), the critical impact of this mockumentary seems limited by the fact that it is framed within TV programs and especially Canal+’s entertainment “philosophy.”